2020
DOI: 10.1155/2020/6506134
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy Observation of Cell and Nerve Density in Different Corneal Regions with Monocular Pterygium

Abstract: Purpose. To investigate the effects of pterygium on corneal cell and nerve density in patients with unilateral pterygium using in vivo laser scanning confocal microscopy (LSCM). Methods. In this cross-sectional study, 24 patients with unilateral pterygium who were treated in the Department of Ophthalmology of the Second People’s Hospital of Wuxi City from April 2018 to July 2018 were analyzed. Each eye with pterygium and its fellow eye were imaged by LSCM. The density of basal corneal epithelial cells, anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In vivo laser scanning confocal microscopy also revealed that the density of corneal basal epithelial cells, anterior stromal cells, endothelial cells, and the length of corneal nerve fibers in the central cornea were higher than in the area near the head of the pterygium. However, dendritic cell density was lower in the former than in the latter (28). Decreased corneal transparency may be due to the irregular arrangement of collagen fibers, uneven distribution of keratocytes, and disruption of the extracellular matrix structure.…”
Section: Discussionmentioning
confidence: 84%
“…In vivo laser scanning confocal microscopy also revealed that the density of corneal basal epithelial cells, anterior stromal cells, endothelial cells, and the length of corneal nerve fibers in the central cornea were higher than in the area near the head of the pterygium. However, dendritic cell density was lower in the former than in the latter (28). Decreased corneal transparency may be due to the irregular arrangement of collagen fibers, uneven distribution of keratocytes, and disruption of the extracellular matrix structure.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that the cornea adjacent to pterygium has a reduction in BCD. 38 The greater localized UV exposure nasally thus cause more damage to the limbal stem cell niche in this location, thus explaining the observed greater reduction of nasal mean BCD in individuals with CUVAF.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, there are no published data that reveal the effects of blepharoptosis on the cornea using IVCM in previous studies. Despite the fact that being to a great extent undetectable on regular assessment procedures, the approach of IVCM has empowered en face assessment of corneal nerves in health and disease [ 4 , 7 ]. Furthermore, some customized software programs have allowed quantification of various aspects of nerve morphology including fibre length, density, width, tortuosity, branching, beading and reflectivity [ 5 , 17 ].…”
Section: Discussionmentioning
confidence: 99%